Studi sejarah perang sebagai basis pengembangan doktrin pertahanan Indonesia: Analisis teoretis dan perbandingan global - Animus Grahadi; Akhmad Zulfikar; Joni Widjayanto (Jurnal Praksis dan Dedikasi Sosial, 2026)
Historical study of warfare as a basis for the development of Indonesia’s defense doctrine: A theoretical analysis and global comparison The study of war history in defense studies is often viewed as a descriptive narrative or a supplement to historiography, so its role in shaping modern defense doctrine has not yet been actively explored. This article analyzes how historical war experience can serve as a source of strategic learning in the development of Indonesia’s defense doctrine. The research uses a qualitative approach, drawing on a literature review and comparing Indonesia’s experiences with those of other countries. The findings show that war history functions not only as a record of events but also as a strategic testing ground that helps identify patterns of doctrinal adaptation to shifts in threats. In the Indonesian context, the experience of the War of Independence not only gave rise to the concept of Total Defense but also shaped a defense logic rooted in community involvement, which remains relevant for addressing hybrid and asymmetric threats. This study highlights that integrating the philosophical, cultural, and practical dimensions of war history strengthens the conceptual basis for developing a national defense doctrine that is flexible and context sensitive. Studi sejarah perang dalam kajian pertahanan kerap ditempatkan sebagai narasi deskriptif atau pelengkap historiografi, sehingga kontribusinya terhadap perumusan doktrin pertahanan kontemporer belum dikaji secara konseptual. Artikel ini bertujuan menganalisis bagaimana sejarah perang dapat diposisikan sebagai sumber pembelajaran strategis dalam pengembangan doktrin pertahanan Indonesia. Penelitian ini menggunakan pendekatan kualitatif melalui analisis literatur dan perbandingan historis antara pengalaman Indonesia dan beberapa negara lain. Hasil kajian menunjukkan bahwa sejarah perang berfungsi tidak hanya sebagai rekaman peristiwa, tetapi sebagai laboratorium strategis yang memungkinkan identifikasi pola adaptasi doktrin terhadap perubahan karakter ancaman. Dalam konteks Indonesia, pengalaman Perang Kemerdekaan tidak sekadar melahirkan konsep Pertahanan Semesta, tetapi juga membentuk logika pertahanan berbasis keterlibatan masyarakat yang relevan untuk menghadapi ancaman hibrida dan asimetris. Studi ini menegaskan bahwa integrasi dimensi filosofis, kultural, dan praktis dalam sejarah perang memperkaya landasan konseptual pengembangan doktrin pertahanan nasional yang adaptif dan kontekstual.